2009
DOI: 10.1007/s10964-009-9487-8
|View full text |Cite
|
Sign up to set email alerts
|

Help-Negation and Suicidal Ideation: The Role of Depression, Anxiety and Hopelessness

Abstract: Help-negation is expressed behaviorally by the refusal or avoidance of available help and cognitively by the inverse relationship between self-reported symptoms of psychological distress and help-seeking intentions. The current study examined the association between suicidal ideation and intentions to seek help from friends, family and professional mental health sources in a sample of 302 Australian university students. Participants were 77.5% female and aged from 18-25 years old, with 85.4% aged 21 years or y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
103
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 63 publications
6
103
0
3
Order By: Relevance
“…It is possible that this may be due to the help negation process. Help negation refers to the inverse relationship that has been observed to exist between psychological distress and help-seeking intention [54], where high levels of psychological distress may influence individuals to discount the benefit of helpseeking. As such, it is possible that higher scores on the K-10, which is indicative of psychological distress, are associated with lower scores on the TAP, indicating more negative beliefs and attitudes toward attending psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this may be due to the help negation process. Help negation refers to the inverse relationship that has been observed to exist between psychological distress and help-seeking intention [54], where high levels of psychological distress may influence individuals to discount the benefit of helpseeking. As such, it is possible that higher scores on the K-10, which is indicative of psychological distress, are associated with lower scores on the TAP, indicating more negative beliefs and attitudes toward attending psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Level of need is controlled by the use of the vignette, which specifies the level of mental health problems for which help is being sought [8 -10]. This approach has increasingly been used to assess mental health literacy and identify factors that are associated with the intention to seek help from informal and professional sources [11][12][13][14][15][16]. The work is based on the theory of planned behavior, which suggests that intention is a good predictor of subsequent behavior if target behavior, time frame, and context are clearly specified [17][18][19].…”
mentioning
confidence: 99%
“…Recently, in a study of young adults (n ϭ 302, 18 -25 years), Wilson and Deane [15] found that higher levels of suicidal ideation were related to lower help-seeking intentions from family, friends, and professional services, and a higher intention to not seek help from anyone. The authors suggested that cognitive distortions experienced by participants with higher levels of suicidal ideation and/or their affective state may impede more rational help-seeking intentions [15].…”
mentioning
confidence: 99%
“…Thus, self-efficacy was directly related to the willingness to seek help, which is consistent with the theoretical construct, since people with higher selfefficacy have more favorable attitudes towards seeking help and to seek help in an optimal manner 21 . On the other hand, those who scored higher in depressive symptomatology were less willing to seek help, which has already been documented in studies with adolescents 22,23 .…”
Section: Discussionmentioning
confidence: 52%